2015
DOI: 10.4103/2141-9248.160176
|View full text |Cite
|
Sign up to set email alerts
|

Hygiene practices among workers in local eateries of Orolu community in south Western Nigeria

Abstract: Background:Activities of local food premises and monitoring of food handlers are usually not regulated.Aim:The objective of this study was to determine food hygiene (FH) practices among food handlers in rural communities in South Western Nigeria.Subjects and Methods:Descriptive cross-sectional study was carried out among 235 food handlers; data collection was by interviewer administered questionnaires. Using the SPSS software, multivariate analysis in two separate models was done to explore the predictors of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
1
7
2
Order By: Relevance
“…Corresponding with our outcomes, a similar study conducted on the street food vendors in Vietnam revealed that vendors had poor food handling practices and operated foods under highly unhygienic conditions (Ngoc & Thanh, 2015). However, this was slightly incongruous with earlier studies in Malaysia (Rahman et al, 2016) and Nigeria (Bamidele et al, 2015) where respondents had above 15% of good hygiene practice. Also, the length of the selling training was not directly related to their knowledge of food safety practices.…”
Section: Discussioncontrasting
confidence: 80%
“…Corresponding with our outcomes, a similar study conducted on the street food vendors in Vietnam revealed that vendors had poor food handling practices and operated foods under highly unhygienic conditions (Ngoc & Thanh, 2015). However, this was slightly incongruous with earlier studies in Malaysia (Rahman et al, 2016) and Nigeria (Bamidele et al, 2015) where respondents had above 15% of good hygiene practice. Also, the length of the selling training was not directly related to their knowledge of food safety practices.…”
Section: Discussioncontrasting
confidence: 80%
“…This may have been due to the high literacy levels of the food vendors surveyed. This finding agrees with results from similar studies in Nigeria and other African countries 16,20,21 but is in contrast with studies carried out in Asian countries where knowledge of food hygiene among the food vendors was abysmally low. 22,23 Majority of the food vendors acquired their knowledge of food hygiene through workshops and seminars which contrasts with findings from other studies where mass media was the common source of information on food hygiene.…”
Section: Discussioncontrasting
confidence: 54%
“…10,11,16,17 However, the food vendors surveyed in Nairobi, Western and Northern Nigeria had no formal education. 15,[18][19][20] In this study more than half of the respondents had a good knowledge of food hygiene with a mean knowledge percentage score of 78%. This may have been due to the high literacy levels of the food vendors surveyed.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, food handlers expressed positive attitude towards food hygiene. Similar studies showed that all participants agree that food handlers should be regularly medically examined (Iwu et al, 2017;Bamidele et al, 2015). It is very important that food safety training programs be implemented for food handlers working in the healthcare sector in Sudan, because education and training in hygienic practices may reduce the morbidity and mortality associated with FBDs in hospitals (Ansari and Khan, 2012).…”
Section: Discussionmentioning
confidence: 84%